Pengaruh literasi keuangan, inklusi keuangan, dan literasi digital terhadap kinerja keuangan UMKM di kota Banjarmasin - Nashoha, Muhammad Rizalun; Rasyid, Muhammad Zakiyyul Fuad; Awwal, Muhammad Al Faridho (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
This study aims to analyze the influence of financial literacy, financial inclusion, and digital literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Banjarmasin City. MSMEs play a vital role in supporting the regional economy; however, they continue to face challenges in financial management and technological adaptation. Improving financial literacy and access to financial and digital resources is believed to be a crucial factor in promoting the growth and sustainability of MSMEs. This research employs a quantitative approach using a survey method. The population consists of all MSME actors operating in Banjarmasin City. A total of 70 respondents were selected through purposive sampling. After undergoing validity and reliability testing, primary data were collected using a structured questionnaire and distributed to MSME owners or managers. Data analysis was conducted using descriptive statistics and multiple linear regression with SmartPLS 4 software. The results indicate that financial literacy, financial inclusion, and digital literacy significantly contribute to the financial performance of MSMEs, both simultaneously and partially, thereby supporting the theoretical framework of the Resource-Based View (RBV).